The Root Zone: Soil Physics and Beyond - Lazarovitch, N. (2020)
Much consensus existed at the conference for a special VZJ section to reflect the importance of the soil root zone from many disciplinary perspectives (soil, environmental, agricultural, hydrologic, and atmospheric) and the complexity of the basic processes involved. The contributions deal with root zone processes at different scales and from different disciplinary viewpoints, while covering a broad range of topics from the very theoretical to important practical applications. Special emphasis is on novel measurement and modeling tools at various scales and the need for interdisciplinary research.